Comparative analysis of five type II TA systems identified in Pseudomonas aeruginosa reveals their contributions to persistence and intracellular survival - Song, Yingjie; Tang, Hong; Bao, Rui (Frontiers in Cellular and Infection Microbiology, 2023)
Background Pseudomonas aeruginosa is a grave nosocomial pathogen that persistently inhabits the lungs of patients with cystic fibrosis (CF) and causes various chronic infections. The bacterial toxin–antitoxin (TA) system is associated with latent and long-term infections, but the underlying mechanisms remain to be fully characterized. Methods We here investigated the diversity and function of five genomic type II TA systems widely distributed among P. aeruginosa clinical isolates. We also examined the distinct structural features of the toxin protein from different TA systems and characterized their contributions to persistence, invasion ability, and intracellular infection caused by P. aeruginosa. Results ParDE, PA1030/PA1029, and HigBA could modulate persister cell formation under treatment with specific antibiotics. Furthermore, cell-based transcriptional and invasion assays revealed that PA1030/PA1029 and HigBA TA systems were critical for intracellular survival. Discussion Our results highlight the prevalence and diverse roles of type II TA systems in P. aeruginosa and evaluate the possibility of using PA1030/PA1029 and HigBA TA pairs as targets for novel antibiotic treatments.